Deep Neck Abscess: Still A Delimma. For Developing Countries: A Prospective Study of 54 Cases - Noor Alarm Ansari, Syed Qaiser Hussain Naqvi, All Raza Brohi, (Journal of Peoples University of Medical & Health Sciences Nawabshah. (JPUMHS), 2012)
Objective: To determine the changing trends with in our population with respect to presentation, etiology, location and microbiology of deep neck abscess (DNAS ). Place & Duration Department of ENT and Head & Neck surgery Peoples University of Medical & Health Sciences Hospital, Nawabshah from Ist May 2011 to 31st December 2011 Patients & Methods: 54clinically confirmed cases of DNAS were included the abases was confirmed by needle aspiration in all cases. Incision & drainage was done at earliest stage & the pus was sent for culture & sensitivity analysis before start of treatment with antibiotics. All patients (except Penicillin sensitive) were initially started on combination of injectable ampicillin, gentamycin and metronidazole. The antibiotics were modified as per culture & sensitivity repots or clinical unresponsiveness ifrequired & the symptomatic treatment was given accordingly. Clinical charts, radiological & bacteriological studies & interventions, along with demographic profile & details of hospital stay were recorded & result were tabulated. Results: Among 54 cases 36(66.6%) were male & 18(33.3%) were female, majority 63% were belong to low socioeconomic strata. Tobacco chewing was the most common addiction followed by smoking, Dental carries was seen in 15 patients and poor dental hygiene in 28 cases, Tooth extraction was found the most predisposing factor. Submandibular region was the most common (37%) site of the abscess & pain was the most common presenting symptom. The culture was positive in 18 cases and staphylococcus aureus was isolated in 15% cases followed by streptococcus in 7% cases. Antibiotic treatment was changed in six patients according to sensitivity reports & was given for maximum for 14 days. All patients recovered fully without complications. Conclusion : We observed that the high incidence ofDNAS could be attributed to the lack of awareness, illiteracy and poverty among patients, along with the poor primary health infrastructure. We also recommend early surgical intervention in these cases to decrease the prevalence of complication.